Non-conventional food plants: research on knowledge and consumption in the region of Brasília-DF (Research, Society and Development, 2022)
Non-conventional food plants (NCFP) are characterized by plant species that have edible parts, but which are generally unknown and are not usually included in the conventional diet of most of the population, except for some regional habits. Therefore, the goal of this research was to analyze the knowledge and consumption of residents of the Federal District, a region with transregional characteristics, to analyze and define the degree of impact that the NCFP have locally. A questionnaire was applied with 23 questions such as: knowledge about NCFP, frequency of consumption, use of edible parts of food, most consumed species, and analysis of the ways of preparation. Moreover, places of purchase, main food fairs, motivation for the consumption of this kind of food, and interest in the knowledge about these foods were also approached on the questionnaire. It was concluded that the consumption of NCFP contributes to the improvement of food safety in the region, due to the stimulus to a healthy and balanced diet that the insertion of vegetables in the eating routine naturally does. There is still a need for better access to scientific knowledge about these species and ways of preparing and consuming these foods.